The memory of pain : women's testimonies of the Holocaust - Loew, Camila. (Value Inquiry Book Series, 2011)
In this book, Camila Loew analyzes four women's testimonial literary writings on the Holocaust to examine and question some of the tenets of the fields of Holocaust studies, gender studies, and testimony. Through a close reading of the works of Charlotte Delbo, Margarete Buber-Neumann, Ruth Klüger, and Marguerite Duras, Loew foregrounds these authors' search for a written form to engage with their experiences of the extreme. Although each chapter contains its individual focus and features, the book possesses a unity in intention, concerns, and consequences. In the theoretical introduction that unites the four chapters, Loew eschews essentialism and revises the emergence of the field of Women and Holocaust studies from the early 1980s on, and signals some of its shortcomings. In response, and in accordance with a recent turn in various disciplines of the Humanities, Loew highlights the ethical dimension of testimony and its responsible commitment to the other. In dealing with the texts as literary testimonies-a complex genre, between literature and history-, testimony is freed from the obligation to respond to the requirements of factual truth, and becomes a privileged form to voice the traumatic event, and to symbolically explore the role of excess.